2020
DOI: 10.1128/msystems.00180-20
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Counterselectable Transposon To Create Markerless Knockouts from an 18,432-Clone Ordered Mycobacterium bovis Bacillus Calmette-Guérin Mutant Resource

Abstract: Mutant resources are essential to improve our understanding of the biology of slow-growing mycobacteria, which include the causative agents of tuberculosis in various species, including humans. The generation of deletion mutants in slow-growing mycobacteria in a gene-by-gene approach in order to make genome-wide ordered mutant resources is still a laborious and costly approach, despite the recent development of improved methods. On the other hand, transposon mutagenesis in combination with Cartesian pooling-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 42 publications
0
14
0
Order By: Relevance
“…A close reading of the original ordered library technique revealed this group also identified “some frequency of picking multiple clones to the same well” due to bacterial clumping, and the authors suggested screening 5 to 10 colonies to obtain a pure clone ( 17 ). In a follow-up study, 11 to 14% of the wells of a Mycobacterium bovis library contained mixed clones ( 37 ). We estimate that the percentage is substantially higher in our library; based on the results in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A close reading of the original ordered library technique revealed this group also identified “some frequency of picking multiple clones to the same well” due to bacterial clumping, and the authors suggested screening 5 to 10 colonies to obtain a pure clone ( 17 ). In a follow-up study, 11 to 14% of the wells of a Mycobacterium bovis library contained mixed clones ( 37 ). We estimate that the percentage is substantially higher in our library; based on the results in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This slow initial growth or small colony size did not necessarily correlate with the robustness of the mutant after restreaking. Borgers et al ( 37 ) found that human hands were more skilled at picking single colonies during library preparation and recommended against using a robot for picking colonies, as we used here. This issue is certainly species dependent, but it seems likely to hold true for P. mirabilis .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our biochemical data support the hypothesis that LamH is responsible for generating the capsular products of LM and LAM. To test this, we utilised a transposon mutant within lamH (BCGDAN_0378) in M. bovis BCG Danish, hereafter referred to as Δ lamH 30 . This species is 99% genetically identical to M. tuberculosis , having lost elements predominantly related to pathogenesis and is generally an excellent model system for M. tuberculosis envelope biogenesis and turnover.…”
Section: Resultsmentioning
confidence: 99%